Personal Learning Networks (PLN) in emerging distance education environments: genesis and dynamics of the PLN in a community of researchers - Oliveira, Nuno Ricardo (2022)
Investigação realizada no âmbito do Doutoramento de Educação, especialidade de Educação a Distância e eLearning (EDeL)